Degradation of biomass fuels during long term storage in indoor and outdoor environments - Graham, Shalini L. (2015)
This project has investigated the degradation of freshly harvested Willow chips, thermally treated wood pellets and white wood pellets in both indoor and outdoor storage. Novel research has been carried out, by combining a range of fuels, storage scenarios, stockpile sizes and weather/seasonal patterns. A wide spectrum of tests was regularly performed on the stored fuel samples, to determine the extent of chemical, mechanical and biological degradation. The storage trials have been divided into Phase 1 and Phase 2, with Phase 1 starting in April 2011 and Phase 2 in November 2011.